2016
DOI: 10.1371/journal.pone.0168339
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum Induces Mild Unfolded Protein Response in Infected Macrophages

Abstract: The Leishmaniases are a group of parasitic diseases caused by protozoa of the Leishmania genus affecting both humans and other vertebrates. Leishmania is an intracellular pathogen able to confer resistance to apoptosis in the early phase of macrophages infection by activation of host PI3K/Akt pathway and inhibition of caspase-3 activation. Intracellular pathogens hijack organelles such as ER to facilitate survival and replication, thus eliciting ER stress and activating/modulating the unfolded protein response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 48 publications
5
59
0
Order By: Relevance
“…More recently, we showed that L. infantum infection induce a mild UPR in U937-derived macrophages [ 68 ], confirming – although with some differences – the activation of IRE1-XBP1 arm of UPR observed in infection by L. amazonensis . Moreover, a potential involvement of the PERK–ATF4 branch of UPR during Leishmania infection was also evidenced since ATF4 , as well as downstream genes such as ATF3 and CHOP were significantly upregulated [ 68 ]. It is known that the PERK/eIF2α/ATF4 pathway plays a key role in autophagy regulation.…”
Section: The Upr In Parasitized Cellssupporting
confidence: 69%
See 2 more Smart Citations
“…More recently, we showed that L. infantum infection induce a mild UPR in U937-derived macrophages [ 68 ], confirming – although with some differences – the activation of IRE1-XBP1 arm of UPR observed in infection by L. amazonensis . Moreover, a potential involvement of the PERK–ATF4 branch of UPR during Leishmania infection was also evidenced since ATF4 , as well as downstream genes such as ATF3 and CHOP were significantly upregulated [ 68 ]. It is known that the PERK/eIF2α/ATF4 pathway plays a key role in autophagy regulation.…”
Section: The Upr In Parasitized Cellssupporting
confidence: 69%
“…showed that L. amazonensis induces autophagy in macrophages and that its inhibition with 3-methyladenine reduced the infection index, suggesting that the autophagic process could provide nutrition to the parasite [ 85 ]. We found that MAP1LC3B was significantly induced in U937-derived macrophages infected by L. infantum [ 68 ]. Therefore, it is likely that also the PERK–ATF4 branch of the UPR could have a role in Leishmania infection (e.g., induction of autophagic process).…”
Section: The Upr In Parasitized Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to intracellular parasites, it has been shown that Plasmodium berghei infection activates the XBP-1 signaling, which favors infection in the liver 15 . Additionally, it was recently reported that Leishmania infantum induces mild ER stress to promote parasite survival 31 . Here, we report that the PERK/eIF2α/ATF4 branch of the IERSR is activated during Leishmania infection and that this signaling has an essential role for parasite survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CHOP was monitored by qPCR using RT 2 SYBR Green ROX FAST Mastermix (Qiagen, Hilden, Germany) in a RotorGene 6000 instrument (Corbett life science, Sydney, Australia), as described previously [103]. A non-template control was included in duplicate for each primer pair reaction, as a negative control.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%